Coarse mineral-associated organic matter is a pivotal fraction for SOM formation and is sensitive to the quality of organic inputs. (October 2020) - Samson, Marie-Élise; Chantigny, Martin H.; Vanasse, Anne; Menasseri-Aubry, Safya; Angers, Denis A.
Abstract: Recent models of soil organic matter (SOM) formation propose that the coarse mineral-associated fraction (coarse-MAOM) could be a pivotal fraction bridging the gap between fresh organic matter inputs and stabilized, mineral-associated SOM. However, little is known about the effect of organic input chemistry and soil texture on the carbon (C) and nitrogen (N) dynamics of this fraction. We studied SOM dynamics in a factorial field experiment comparing 10 combinations of crop residue management (retained or exported) with different fertilizer sources, including solid poultry, liquid dairy and liquid swine manure, a mineral fertilizer (NPK), and a control without N (PK) in two soils with contrasted texture. After 9 y of management, we compared the distribution of C and N within the light fraction (LF), the coarse-MAOM, and the fine mineral-associated organic matter fraction (fine-MAOM) of surface (0–5 cm) soil. We found that retention of mature crop residues increased soil C content through an increase in LF and coarse-MAOM but did not influence N content in any fractions. Conversely, the fertilizer source influenced C and N accumulation in the coarse- and fine-MAOM in the silty clay soil where greater values were generally found with poultry and liquid dairy manures. Similar trends were found in the sandy loam soil, but statistically significant differences were only found for C in the coarse-MAOM fraction. The coarse-MAOM fraction had a much lower C:N ratio (15–16) than LF (26–36) and appeared generally responsive to the different organic inputs. Despite its limited size (∼10% of total soil organic carbon), coarse-MAOM appeared to represent a central location for the formation of new SOM and for the accumulation of C and N following fresh organic inputs. We therefore propose that it is considered in models as a pivotal fraction of SOM formation in arable soils. Graphical abstract: Schematic of SOM formation and stabilization, emphasizing the relevance of subdividing particulate organic matter (POM) into light (LF) and heavy (coarse-MAOM) material to better highlight the impact of different organic inputs on SOM formation in different fractions. In our study, mature crop residues mainly entered the soil as LF and then coarse-MAOM, with no impact on the size of the fine-MAOM fraction. In contrast, C and N from animal manures were directly incorporated within the coarse-MAOM fraction and, in the fine-textured soils, contributed to increase the amounts of C and N in the fine-MAOM fraction, presumably directly because of the presence of organic N in the manures, or indirectly through aging and fragmentation of coarse-MAOM complexes. Image 1 Highlights: The coarse-MAOM was responsive to the different organic inputs in the sandy and clayey soil. The coarse-MAOM fraction had a much lower C:N ratio (15–16) than LF (26–36). Mature crop residues increased C content of the LF and coarse-MAOM. Poultry and dairy manures increased C and N in coarse- and fine-MAOM in the clayey soil. Coarse-MAOM is a pivotal fraction in the formation of new SOM as a function of organic input biochemistry.